Hubungan Pengetahuan dengan Perilaku Pencegahan Gastritis pada Mahasiswa - Pomarida Simbolon; Nagoklan Simbolon (Poltekkes Kemenkes Maluku, 2022)
Gastritis or dyspepsia, a term often known by the public as gastritis or gastric disease, is a collection of facts accepted as heartburn. Gastritis in the community, especially in teenagers or students, is a very common suffered which can be influenced by factors of knowledge and behavior to prevent gastritis. This research aims to determine the relationship of knowledge with the behavior of gastritis prevention in students at Saint Elisabeth School of Health Sciences Medan. This research design uses descriptive-analytic with a cross-sectional study. The sampling technique used is purposive sampling with a sample of 32 people. The research instrument used is a questionnaire. The result of this study shows that students have enough knowledge about gastritis (50%) and have enough gastritis prevention behaviors (56,3%). Data analysis with the Chi-square test obtained a p-value = 0.046, where p<0.05 indicates a significant positive relationship between knowledge and gastritis prevention behavior in STIKes Santa Elisabeth Medan students in 2020. Each student is expected to improve knowledge and gastritis prevention behavior to avoid things that harm themselves and others.